The new Chinese : how they are shaping Australia - Li, Barry (John Wiley & Sons Australia, Ltd, 2017)
BRIDGE THE GAP BETWEEN THE CHINA YOU KNOW AND THE REAL CHINA OF TODAY In the last 30 years, China has transformed itself into one of the world's leaders in political, economic and social relations. With Australia a hotspot for Chinese immigrants, understanding the cultural nuances, both from an Australian and a Chinese perspective, is now more important than ever. Your next hire or business deal could depend on it. Australia is a young country built on immigration and cultural assimilation, and whether they are new immigrants or Australian born, in the workforce or the property market, or in the suburbs or the city, the 'new Chinese' are now an integral part of this culture. Told through the personal story of author Barry Li, The New Chinese reveals: -how to navigate cultural differences between Australia and China -what four generations of Chinese are present in Australia -why political sensitivities should be observed by those doing business with China -how Chinese consumers and investors spend their wealth -what challenges are in store for China's future. The New Chinese is your essential guide to the history, culture, and mindset of Chinese migrants in Australia, and of the new China.